The carrier wave : - Hall, Peter (Unwin Hyman, 1988)
Part one The Kondratieff waves; Part two The mechanical age: New IT in the second Kondratieff, 1846-95; Part three The electrical age: New IT in the third Kondratieff, 1896-1947